Теоретико-оптимізаційний апарат скорочення витрат у задачах визначення раціональної кількості матеріальних запасів будівельних підприємств - Антипенко, Є. Ю. (Ways to Improve Construction Efficiency, 2014)
The article discusses the issues of improving resource management techniques and approaches to the definition of control parameters and certain types of costs in connection with the definition of the optimal size of the order of material - raw materials in the supply chain management of construction enterprises. Approaches to determine the optimal size of the order of the required material - natural resources by taking into account the level of costs that arise in this and approaches to the definition of optimality criteria material procurement processes - raw materials and a corresponding decrease in the cost of production.